Salicylic acid improves Nasturtium officinale phytoremediation capability for cadmium-contaminated paddy soils - Zheng, Yangxia; Zhang, Ran; Zhu, Ying; Ao, Qiaoman; Liu, Han; Li, Aihui; Lin, Lijin; Wang, Li (Frontiers in Plant Science, 2022)
Cadmium (Cd) contamination is a severe problem in paddy soils that has affected crops' safety. The present study aimed at remediating Cd-contaminated paddy soil by improving the phytoremediation capability of aquatic accumulator plants. We conducted a experiment to investigate the effects of salicylic acid (SA) on the growth and Cd phytoremediation capability of the aquatic accumulator plant Nasturtium officinale. SA with the concentrations of 100, 150, and 200 mg/L increased the root and shoot biomass of N. officinale, while only 150 mg/L increased the chlorophyll a and b contents. SA increased the activities of peroxidase and catalase of N. officinale to a great extent, but decreased the superoxide dismutase activity and soluble protein content. SA also increased the root Cd content, shoot Cd content, root Cd extraction, and shoot Cd extraction to a large extent. At concentrations of 100, 150, and 200 mg/L, SA increased the shoot Cd extraction by 17.59%, 47.16%, and 43.27%, respectively, compared with the control. Moreover, SA concentration had a quadratic polynomial regression relationship with the root Cd extraction and shoot Cd extraction. The correlation and grey relational analyses revealed that root Cd extraction, shoot biomass, and root biomass were closely associated with shoot Cd extraction of N. officinale. Thus, our results suggest that SA promoted the growth and improved the phytoremediation (extraction) capability of N. officinale, and 150 mg/L SA was the most suitable concentration.